Stuart Hall as a criminological theorist-activist - Murji, Karim (Theoretical criminology, 2020)
What is the legacy of Stuart Hall for criminology, beyond just Policing the Crisis? In this article I highlight two other engagements by Hall in race and policing one in the 1980s through an independent inquiry, the other in the 1990s through a major public inquiry. Beyond bringing this work to light, this article shows how these engagements reveal Hall’s unique style of theorizing the concrete politics of the present through his stress upon conjunctures and context, and via the concept of articulation. Hall’s interventions in these two cases underscore an analytical and theoretical stance in public forums that made him more than a ‘scholar-activist’ but rather a ‘theorist-activist’ who drew on theory for strategic and ‘applied’ purposes. The ways in which he did this can, I suggest, point to different ways of ‘doing race’ in a critical criminology.